Computer networks : 21st International Conference, CN 2014, Brunow, Poland, June 23-27, 2014. Proceedings - Gaj, Piotr; Stera, Piotr; Kwiecien, Andrzej (Communications in Computer and Information Science, 2014)
This book constitutes the thoroughly refereed proceedings of the 21st International Conference on Computer Networks, CN 2014, held in Brunów, Poland, in June 2014. The 34 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers in these proceedings cover the following topics: computer networks, tele informatics and communications, new technologies, queueing theory, innovative applications and networked and IT-related aspects of e-business.